A Analysis Of Factors Influencing The Purchase Decision Of Fast Food Fried Chicken Case Study McDonald’s in Ambon City - Harold Blenco Laisina; Leunard O. Kakisina; Maise T. F. Tuhumury (International journal of technology and education research, 2026)
This study aims to identify the factors influencing the decision to purchase fast-food fried chicken at McDonald’s in Ambon City. This study employs a quantitative method using convenience sampling to select 100 respondents who are McDonald’s customers in Ambon City. The data used consists of primary data collected via questionnaires and secondary data from various sources. Data analysis was conducted using multiple linear regression. The factors influencing purchasing decisions include cultural, social, and personal factors. In general, cultural and personal factors have a more dominant influence compared to social factors. Cultural factors are reflected in modern lifestyles and practical consumption habits, while personal factors relate to individual needs, desires, and satisfaction. Meanwhile, social factors, such as the influence of friends and family, tend to have a lower impact. In conclusion, the findings indicate that the decision to purchase fast-food fried chicken at McDonald’s in Ambon City is primarily influenced by cultural, personal, and social factors. Modern lifestyles, practical consumption habits, and individual needs and satisfaction are the key factors driving consumer purchasing decisions.